2016
DOI: 10.1371/journal.pone.0153497
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating Serum miR-34a and miR-122 with Dyslipidemia among Patients with Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) covers a spectrum of diseases from simple steatosis to non-alcoholic steatohepatitis, with approximately 20% risk of progressing to fibrosis and cirrhosis. The aim of this study was to compare the relative expression levels of circulating miR-21, miR-34a, miR-122, miR-125b and miR-375 between healthy controls and NAFLD patients, and to assess the feasibility of microRNAs as potential biomarkers for NAFLD. A cross-sectional study was conducted to evaluate circulating se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
4
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 38 publications
(44 reference statements)
3
129
4
2
Order By: Relevance
“…We also found miR‐34a‐5p and miR‐365a‐3p to be up‐regulated in serum of CFLD compared to CFnoLD children. Increased serum levels of miR‐34a have been reported in CLDs such as hepatitis C and NAFLD . miR‐34a has been associated with liver regeneration, having a direct repressor effect on hepatocyte proliferation and senescence in alcoholic liver injury and in animal models of partial hepatectomy .…”
Section: Discussionmentioning
confidence: 99%
“…We also found miR‐34a‐5p and miR‐365a‐3p to be up‐regulated in serum of CFLD compared to CFnoLD children. Increased serum levels of miR‐34a have been reported in CLDs such as hepatitis C and NAFLD . miR‐34a has been associated with liver regeneration, having a direct repressor effect on hepatocyte proliferation and senescence in alcoholic liver injury and in animal models of partial hepatectomy .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, elevated miR-122 and miR-34a (another RYGB-downregulated miRNA in this study) have been associated with dyslipidemia in patients with non-alcoholic fatty liver disease. 33 In addition, miR-34a was reported as the most highly expressed hepatic miRNA in obese mice, where it impaired physiological postprandial responses through attenuation of FGF19 by directly targeting β-Klotho. 34 Our study demonstrated significant correlations between the change in circulating levels of miR-122 and miR-34a and the change in S G (Figures 3b and c), and between the changes in miR-34a and AIRg (Figure 3d).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed that liver cells release exosomes, containing miRNAs, as a defense mechanism [29,30,31]. Various studies have shown that miR-122 is released after chronic and acute liver damage [32,33,34]. However, due to different stimulants, miR-122 is released under different formations.…”
Section: Exosome-mediated Regulatory Effects In Livermentioning
confidence: 99%